Titanium imido complexes with 1,3,5-triazacyclohexane ligands: syntheses, solution dynamics and solid state structures - Wilson, P; Cooke, P; Blake, A; Mountford, P; Schroder, M (1999)
The multi-gram scale syntheses of the first 1,3,5-triazacyclohexane imido complexes ]Ti(NR)(R' 3tach)Cl 2] (R=Bu(t), C 6H 3Pr 2/ 1-2,6; R' = Me, Bu(t)) are described together with the X-ray structures of [Ti(NBu(t))(Me 3tach)Cl 2] and ]Ti(NBu(t))(Bu 3/(t)tach)Cl 2]; the complexes of Me 3tach exhibit dynamic NMR behaviour via an unusual trigonal twist of the facially coordinated Me 3tach ligand (Me 3tach and Bu(t) 3tach = 1,3,5- trimethyl- and tri-tert-butyl-1,3,5-triazacyclohexane, respectively).